2010
DOI: 10.1186/1471-2458-10-12
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes mellitus and hypertension have comparable adverse effects on health-related quality of life

Abstract: BackgroundWe aimed to assess health-related quality of life (HRQoL) among people with diabetes or hypertension, estimate the effect of cardiovascular comorbidities on HRQoL as well as compare HRQoL in these groups with that of healthy individuals.MethodsA total of 9,070 respondents aged 18 years and over were assessed for HRQoL. Data were obtained from the Croatian Adult Health Survey. Respondents were divided into five groups according to their medical history: participants with hypertension (RR), hypertensio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
57
4
5

Year Published

2012
2012
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(77 citation statements)
references
References 26 publications
11
57
4
5
Order By: Relevance
“…[7] In another study to evaluate the health related aspects of life and diabetic patients reported comparably limited health related aspects of life, as compared to healthy individuals. [8] Similar results were obtained when HRQoL was assessed in hypertensive sufferer. [9] Fahad Saleem et al reported in a study that health related characteristics of life in hypertensive patients of Quetta, Pakistan are poor which also supports of my claim of study.…”
Section: Discussionsupporting
confidence: 71%
“…[7] In another study to evaluate the health related aspects of life and diabetic patients reported comparably limited health related aspects of life, as compared to healthy individuals. [8] Similar results were obtained when HRQoL was assessed in hypertensive sufferer. [9] Fahad Saleem et al reported in a study that health related characteristics of life in hypertensive patients of Quetta, Pakistan are poor which also supports of my claim of study.…”
Section: Discussionsupporting
confidence: 71%
“…(11) Poljičanin et al suggested that hypertensive patients have the perception of being chronically sick, therefore, they feel more fragile, which ends up negatively affecting their quality of life. (20) The perception of having a chronic disease may be related to the problems faced by these individuals in self-care activities, such as in blood pressure control, nutrition, weight control, care of stress and physical activity. (21) Within this context, a prevalence study was carried out in 2010 with 385 hypertensive in two hospitals that serve 70% of the Pakistani population.…”
Section: Discussionmentioning
confidence: 99%
“…It shows that participants with hypertension reported comparably limited HRQL in all dimensions of SF-36, compared with healthy individuals and this explains that this condition impose negative limitations in physical and mental functioning as found in the study carried out by Poljičanin, Tamara et al [10]. However, available literature [11] showed that hypertension had a little association with mobility and physical activities and it is more strongly related to anxiety and depression, while our study found that patients with hypertension had lower scores in all scales of SF-36, even the physical health.…”
Section: Discussionmentioning
confidence: 54%
“…There have been number of studies examining the impact of cardiovascular diseases either single or co-morbid conditions on the HRQL, especially the co-morbidity of hypertension [9,10]. However, none of these studies aimed to elicit this problem in people with hypertension in the UAE.…”
Section: Introductionmentioning
confidence: 99%